Lily Poisoning in Domestic Cats - Panziera, Welden; Schwertz, Claiton Ismael; Henker, Luan Cleber; Konradt, Guilherme; Bassuino, Daniele Mariath; Fett, Rochana Rodrigues; Driemeier, David; Sonne, Luciana (Acta Scientiae Veterinariae, 2019)
Background: Cases of plant intoxication in small animals are observed frequently in the domestic environment, mainly because most dogs and cats live in households and occasionally have access to streets and rural areas. Among such toxic agents, ornamental plants of the genus Lilium and Hemerocallis, which are potentially nephrotoxic to the feline species, are highlighted. Affected cats start presenting clinical signs 1-6 h after plant ingestion. Renal failure takes place in 12-72 h, and death may occur in an interval ranging from three to seven days. The objective of this article is to describe the epidemiological, clinical and pathological findings of lily (Lilium sp.) poisoning in two cats. Case: The aspects of lily poisoning in two cats are described (cat #1 and cat #2). Cat #1 was a 3-year-old, mixed breed female cat, which presented a clinical history of anorexia, apathy, drooling, vomiting and polydipsia. Serum biochemical analysis revealed creatinine elevation (21.2 mg/dL), as well as hyperphosphatemia (19 mg/dL). Seventy-two h after the onset of clinical signs, renal failure progressed to anuria, followed by death. The second animal of this report (cat #2) was a 2-year-old, mixed-breed male cat. The animal was found dead by the owner without displaying any previous clinical signs. Cats #1 and #2 ingested leaves of lily, which were present in their households as ornamental plants. At necropsy, the kidneys of both cats presented mild enlargement. Moderate perirenal edema was also noted. Cat #1 showed morphologic extrarenal uremic lesions, characterized by ulcers in the oral mucosa and in the margin of the tongue ventral surface. Microscopic lesions observed in both cases were similar and compatible with acute toxic nephropathy. Histologically, severe epithelial cell degeneration and necrosis of proximal and distal convoluted tubules were noted. Other renal microscopic findings included hyaline and granular casts, tubule regeneration and occasional birefringent oxalate crystals. Cat #1 also presented moderate white matter vacuolation in the telencephalon and cerebellum. Discussion: The epidemiologic, clinical and pathological findings reported in the present study are similar to previous descriptions of lily poisoning in cats. Lily poisoning has been described in both males and females, without breed and age predisposition, similarly to what has been found in the present study. Kidney metabolite excretion, including the elimination of molecules such as creatinine, urea, and phosphorus is usually compromised in these cases, which was noted in cat #1. The same animal showed extrarenal manifestations of renal failure, leading to a clinical presentation of uremic syndrome, which is not frequent in these intoxications. Animals intoxicated by lily usually die from renal failure and anuria. In most cases, lesions are restricted to the kidneys. In the reported cases, the microscopical lesions consisted of tubule epithelial cells degenerative changes and necrosis. Acute lily intoxication in cats must be differentiated from other conditions, such as intoxications due to aminoglycoside antibiotics, heavy metals, nonsteroidal anti-inflammatory drugs, antifungal agents, chemotherapeutic drugs, and ethylene glycol. The knowledge regarding the toxic potential of ornamental plants is fundamental in order to prevent such events of intoxication, as well as to reach the final diagnosis. Epidemiological, clinical and pathological findings were essential to conclude the final diagnosis.